2019
DOI: 10.1021/acsaem.9b01341
|View full text |Cite
|
Sign up to set email alerts
|

π-Extended cis-Configured Unsymmetrical Squaraine Dyes for Dye-Sensitized Solar Cells: Panchromatic Response

Abstract: Light absorbing sensitizer is the heart of the third generation photovoltaic technologies such as dye-sensitized solar cells. Despite possessing large extinction coefficients for the metal-free organic dyes, the light-harvesting efficiency is limited with the narrow absorption profile in either visible or NIR regions of the solar spectrum. Though monolayer formation of organic sensitizers on semiconducting metal oxide surface leads to dye–dye interaction that leads to broadening the absorption profile, the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 56 publications
(78 reference statements)
1
20
0
Order By: Relevance
“…These effects are due to the alteration of energy transfer pathways. 53,82,[94][95][96][97] Conformers have also been shown to change transition dipole orientation, further potentially affecting exciton delocalization. 98 Certain applications may benet from different conformers, such as dye-sensitized solar cells in part because of accommodation of different anchoring options on substrates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These effects are due to the alteration of energy transfer pathways. 53,82,[94][95][96][97] Conformers have also been shown to change transition dipole orientation, further potentially affecting exciton delocalization. 98 Certain applications may benet from different conformers, such as dye-sensitized solar cells in part because of accommodation of different anchoring options on substrates.…”
Section: Discussionmentioning
confidence: 99%
“…50 They can potentially be structurally tailored for a wide variety of applications. [51][52][53] First synthesized by Treibs and Jacobs, 54 the central feature of SQ dyes includes an electron-decient squaric moiety, combined with electron-rich groups in a symmetric manner by means of a methine bridge. 52 The photophysical features and extensive structural tunability make squaraines well-suited candidates for the investigation of exciton delocalization when assembled.…”
Section: Introductionmentioning
confidence: 99%
“…Due to a modest photovoltage (577 mV) – as is common in the NIR region with dye sensitized solar cells – the overall power conversion efficiency was limited to 6.9% PCE. 317 An ethyl cyanoacetate-derived squaraine dye (HSQ4) with dual anchors was shown to have a substantially increased stability relative to mono-anchored squaraine dyes with no change in PCE after 1000 hours. 318 In this same study, the ethyl cyanoacetate group was found to give a dye with a significantly higher excited state oxidation potential than a dicyanomethylene derived dye, which correlated to a higher IPCE peak value (80% versus 70%).…”
Section: Methodsmentioning
confidence: 99%
“…These redox potentials are well-matched with the conduction band of TiO 2 and the redox potential values of iodide/tri-iodide electrolyte, which is energetically helpful for electron injection and dye-regeneration. 31…”
Section: Spectroelectrochemical Propertiesmentioning
confidence: 99%